Inexpressible privacy : the interior life of antebellum American literature - Shamir, Milette (University of Pennsylvania Press, 2006)
Few concepts are more widely discussed or more passionately invoked in American public culture than the concept of privacy. Milette Shamir traces the peculiarly American obsession with privacy back to the middle decades of the nineteenth century, when our modern understanding of the concept took hold.